SELEKSI DAN PEROLEHAN GENETIK PADA KEBUN BENIH SEMAI GENERASI KETIGA Acacia mangium - Betty Rahma Handayani; Sri Sunarti; Arif Nirsatmanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2017)
One of the purposes of seedling seed orchard (SSO) establishment is to produce genetically improved seeds. The amount of genetic gain in the SSO is determined from a series of selection involving within and between family selection in which the gain is generally achieved from the accumulated increases of gain in successive advanced generation breeding cycles. In present study, the amount of genetic gain was predicted in third-generation SSO of Acacia mangium after first within-plot selection using a retrospective selection index’s method. The SSO was established in Wonogiri, Central Java which was laid out in a randomized complete block design, 65 families, six replications, four trees-line plot and spacing of 2 m x 4 m. Actual within-plot selection was subjectively practiced in 40 months after planting. The observed traits for genetic gain prediction was height, diameter at breast height (dbh), and stem straightness using data collected at 24 months after planting. For calculating genetic gain based on multiple trait selection index, coefficient weight for each trait was then derived from the selection differential. The results of study showed that the first within plot selection was practiced mostly for imposing dbh rather than height or stem straightness with the relative gain was 6% for dbh, and 3% for both height and stem straightness. Using the derived coefficient weight, the expected genetic gain by family selection was found to be slightly lower than those predicted by within-plot selection at 3% for dbh, and 2% for both height and stem straightness.